The variation of soil physical properties in fertile well-drained soils under banana - Leummens, H.J.L. (1993)
90 pág, 16 ilus, 10 tab, 42 ref. También como: Field Report - Atlantic Zone Programme (CATIE-AUW-MAG) no. 115